2016
DOI: 10.1016/j.nicl.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state fMRI study of acute migraine treatment with kinetic oscillation stimulation in nasal cavity

Abstract: Kinetic oscillatory stimulation (KOS) in the nasal cavity is a non-invasive cranial nerve stimulation method with promising efficacy for acute migraine and other inflammatory disorders. For a better understanding of the underlying neurophysiological mechanisms of KOS treatment, we conducted a resting-state functional magnetic resonance imaging (fMRI) study of 10 acute migraine patients and 10 normal control subjects during KOS treatment in a 3 T clinical MRI scanner. The fMRI data were first processed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Such transition of brain states has been confirmed in both animal models and humans ( Majeed et al, 2011 ). Dynamic functional connectivity analysis has shown that the spontaneous transitions between networks of interacting brain areas are highly organized into a hierarchy of two types of metastates: one for higher order cognition, and the other for the sensorimotor systems ( Li et al, 2016 ). The transitions are more probable within, than between, metastates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such transition of brain states has been confirmed in both animal models and humans ( Majeed et al, 2011 ). Dynamic functional connectivity analysis has shown that the spontaneous transitions between networks of interacting brain areas are highly organized into a hierarchy of two types of metastates: one for higher order cognition, and the other for the sensorimotor systems ( Li et al, 2016 ). The transitions are more probable within, than between, metastates.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains largely unclear whether deficiency is present in the dynamic interactions between RFNs or between brain areas within a given RFN. In this study, we incorporated sliding window analysis of time-varying connectivity hierarchy (SWATCH) into previously developed quantitative data-driven analysis framework ( Li et al, 2016 ; Nordin et al, 2016 ) to assess functional connectivity both in the entire data acquisition period (assumed stationary) and a 2-min sliding window in a voxel-wise fashion. With the SWATCH analysis, we can derive two types of functional connectivity metrics, namely the functional connectivity strength index (CSI) and connectivity count index (CCI) as well as the temporal means of their sliding-window time series from the acquired resting-state fMRI data.…”
Section: Introductionmentioning
confidence: 99%
“…It should be acknowledged that the mechanism leading to the beneficial effects seen in these relatively small studies with KOS is not well understood, but indirect effects on the autonomic nervous system may play a role (Li, Wang, Hallin, & Juto, ). It can be hypothesized that the pronounced reduction of HRV is either linked to an effect by KOS on breathing pattern or to a change in autonomic tone, through the so‐called trigemino‐cardiac reflex (Lemaitre, Chowdhury, & Schaller, ).…”
Section: Discussionmentioning
confidence: 99%
“…The VNS device we used had not previously been applied in a study focusing on inflammatory response. Thus it may not have been effective enough despite the HRV results in healthy volunteers and reported influence on autonomic nervous system activity when used in a study on migraines [ 130 ]. However, we did not record any significant changes in HRV in patients during this study.…”
Section: Cap and Ckdmentioning
confidence: 99%